2020
DOI: 10.3389/fimmu.2020.02081
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Eight-Negative Kinase 1 Is a Mediator of Acute Kidney Injury in Experimental and Clinical Traumatic Hemorrhagic Shock

Abstract: Trauma represents a major socioeconomic burden worldwide. After a severe injury, hemorrhagic shock (HS) as a frequent concomitant aspect is a central driver of systemic inflammation and organ damage. The kidney is often strongly affected by traumatic-HS, and acute kidney injury (AKI) poses the patient at great risk for adverse outcome. Recently, thirty-eight-negative kinase 1 (TNK1) was proposed to play a detrimental role in organ damage after trauma/HS. Therefore, we aimed to assess the role of TNK1 in HS-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Once expressed, this kinase exhibits maximum catalytic activity (Armacki et al 2018). TNK1 is moderately expressed in the kidney, and its expression has been shown to be upregulated in several animal models of HS/trauma (Hoehn et al 1996;Halbgebauer et al 2020). Likewise, our study showed that HS induced renal expression of TNK1 in rats, accompanied by the development of kidney injury.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Once expressed, this kinase exhibits maximum catalytic activity (Armacki et al 2018). TNK1 is moderately expressed in the kidney, and its expression has been shown to be upregulated in several animal models of HS/trauma (Hoehn et al 1996;Halbgebauer et al 2020). Likewise, our study showed that HS induced renal expression of TNK1 in rats, accompanied by the development of kidney injury.…”
Section: Discussionsupporting
confidence: 63%
“…This gene is originally cloned from CD34 þ /Lin-/CD38-hematopoietic stem/progenitor cells (Hoehn et al 1996). Renal expression of TNK1 is significantly upregulated in experimental HS in mice and non-human primates as well as patients with severe trauma, and closely associated with the severity of inflammation and kidney injury (Halbgebauer et al 2020). It is reported that TNK1 plays an important role in inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 plays a prominent role in the differentiation from Th1 to Th2 in the development of HS ( 67 ). The secretion of IL-6 is positively correlated with the prognosis patients with shock and organ dysfunction ( 68 , 69 ). Zhang Yong et al.…”
Section: New Insights Into Hs Therapeutics With Innate Immune Regulationmentioning
confidence: 99%
“…THS-induced injury is accompanied by immune dysfunction exhibited by excessively inflammasomes release and multiple inflammatory signaling pathways activation. These events lead to an immune-suppressive state and host defense failure, eventually giving rise to inflammation-mediated infection and organ dysfunction ( 2 , 4 ). Therefore, clinical treatments to block immune disorders and prevent organ damage are urgently needed and will have a significant global impact on patient outcomes after THS.…”
Section: Introductionmentioning
confidence: 99%